IGF2BP3 From Physiology to Cancer: Novel Discoveries, Unsolved Issues, and Future Perspectives - Mancarella, Caterina; Scotlandi, Katia (Frontiers in Cell and Developmental Biology, 2020)
RNA network control is a key aspect of proper cellular homeostasis. In this context, RNA-binding proteins (RBPs) play a major role as regulators of the RNA life cycle due to their capability to bind to RNA sequences and precisely direct nuclear export, translation/degradation rates, and the intracellular localization of their target transcripts. Alterations in RBP expression or functions result in aberrant RNA translation and may drive the emergence and progression of several pathological conditions, including cancer. Among the RBPs, insulin-like growth factor 2 mRNA-binding protein 3 (IGF2BP3) is of particular interest in tumorigenesis and tumor progression. This review highlights the molecular mechanisms underlying the oncogenic functions of IGF2BP3, summarizes the therapeutic potential related to its inhibition and notes the fundamental issues that remain unanswered. To fully exploit IGF2BP3 for tumor diagnosis and therapy, it is crucial to dissect the mechanisms governing IGF2BP3 re-expression and to elucidate the complex interactions between IGF2BP3 and its target mRNAs as normal cells become tumor cells.